2002
DOI: 10.1677/joe.0.1720507
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin blocks pre-partum nest building behaviour in the pig (Sus scrofa): effects on plasma prostaglandin F metabolite, oxytocin, cortisol and progesterone

Abstract: In the pig, nest building occurs in the day preceding parturition (gestation=114-116 days). Nest building behaviour can be induced in pregnant, pseudopregnant and cyclic female pigs following injection of prostaglandin F2 . Here we investigated behaviour and endocrine changes after the administration of indomethacin, which inhibits cyclo-oxygenase enzymes and thus prostaglandin synthesis.In experiment 1, pregnant primiparous pigs (gilts) were blood sampled through jugular vein catheters every 20 min from 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The plasma oxytocin concentration (measured hourly) increased during farrowing, and maximum concentrations were reached late in the farrowing rather than in the beginning. Plasma oxytocin has been reported to increase as farrowing approach [measured the last 24 h prepartum in Gilbert et al (2002) and the last 5 h prepartum in Damm et al (2003)] and also to increase immediately after each fetal expulsion [measured, however, only until 140 min after BFP in Gilbert et al (1994)]. Thus, the continued oxytocin rise in our study may reflect the accumulation of several fetal expulsions.…”
Section: Discussionmentioning
confidence: 49%
“…The plasma oxytocin concentration (measured hourly) increased during farrowing, and maximum concentrations were reached late in the farrowing rather than in the beginning. Plasma oxytocin has been reported to increase as farrowing approach [measured the last 24 h prepartum in Gilbert et al (2002) and the last 5 h prepartum in Damm et al (2003)] and also to increase immediately after each fetal expulsion [measured, however, only until 140 min after BFP in Gilbert et al (1994)]. Thus, the continued oxytocin rise in our study may reflect the accumulation of several fetal expulsions.…”
Section: Discussionmentioning
confidence: 49%
“…As well as reducing pain and inflammation by reducing prostaglandin and thromboxane through the inhibition of cyclooxygenase (COX) enzymes ( 29 ), NSAIDs could also inhibit parturition, as prostaglandin increases toward the onset of farrowing and peaks at the time of birth ( 30 ). When the NSAID indomethacin was administered at the onset of nest-building in sows, nest-building behavior was reduced, and parturition tended to be delayed ( 46 ). In addition, NSAIDs can cross the placenta, which can result in detrimental side effects for the unborn fetus, where prostaglandins play an important role in developmental and physiological regulation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A rise in plasma concentrations of prolactin is known to initiate NB behaviour in prepartum sows ( Widowski and Curtis, 1990 ; Castrén et al, 1993 ; Algers and Uvnas-Moberg, 2007 ), while the onset of prepartum NB behaviour has not been directly related to plasma oxytocin concentrations in the sow ( Boulton et al, 1997 ; Gilbert et al, 2002 ). In contrast, several studies have suggested that prolactin concentrations in prepartum sows might not be correlated with the degree of NB behaviour ( Lawrence et al, 1994 ), and played only a limited role in preparturient activity of sows ( Rushen et al, 2001 ).…”
Section: Interrelations Between Nest-building Behaviour and Endogenoumentioning
confidence: 99%